Analysis of the performance rate variations of schools contemplated with the School Cistern Program in the valleys of Jequitinhonha and Mucuri (Research, Society and Development, 2021)
The aim of the study was to analyze the variations in students’ performance rates in schools int the Jequitinhonha and Mucuri Valleys, in the Brazilian state of Minas Gerais, contemplated by the School Cistern Program. The survey of the schools contemplated by the Program was carried out with documental research of spreadsheets provided by the Brazilian Semi-arid Articulation. The data about school failure and dropout rates were collected from the Instituto Anísio Teixeira (INEP), and made available on the Qedu website. The non-parametric Wilcoxon test was used for testing averages. As means of school performance rates in the periods before and after the installation of the cistern in schools, they were not different.  Thus, the expectation of an improvement in school performance rates through the Program was not evident. Thus, the present study shows that there are factors that still need to be studied and treated for the School Cistern Program to reach its objective of improving school performance rates in the region of the Jequitinhonha and Mucuri valleys.